2014
DOI: 10.1177/0020764014535758
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hikikomori syndrome of social withdrawal: Psychosocial features and treatment preferences in four countries

Abstract: Background-Hikikomori, a form of social withdrawal first reported in Japan, may exist globally but cross-national studies of cases of hikikomori are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
194
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(210 citation statements)
references
References 28 publications
8
194
1
7
Order By: Relevance
“…On the other hand, hikikomori-like cases have recently been reported in other countries of varying sociocultural and economic backgrounds such as Hong Kong, Oman and Spain, and our studies based on structured interviews have revealed the existence of hikikomori in India, South Korea and the US 4 . Thus, hikikomori has now crossed the limits of a culturebound phenomenon to become an increasingly prevalent international condition.…”
Section: Claudia Catanisupporting
confidence: 51%
See 2 more Smart Citations
“…On the other hand, hikikomori-like cases have recently been reported in other countries of varying sociocultural and economic backgrounds such as Hong Kong, Oman and Spain, and our studies based on structured interviews have revealed the existence of hikikomori in India, South Korea and the US 4 . Thus, hikikomori has now crossed the limits of a culturebound phenomenon to become an increasingly prevalent international condition.…”
Section: Claudia Catanisupporting
confidence: 51%
“…In 2010, Japan's Ministry of Health, Labour and Welfare announced a guideline for hikikomori which included a definition ("a situation where a person without psychosis is withdrawn into his/her home for more than six months and does not participate in society such as attending school and/or work") 3 . More recently, in order not only to diagnose but also to assess the severity of the condition, we proposed even more precise diagnostic criteria based on the levels of physical isolation at home, avoidance of social interactions, and functional impairment or distress, as well as a sustained duration of six months or more 4 .…”
Section: Claudia Catanimentioning
confidence: 99%
See 1 more Smart Citation
“…29) In the past people believed hikikomori was a social phenomenon exclusive to the Japanese culture but the similar phenomenon is seen in Korea, India, and the United States. 30) Because the standard for ego-identity have become more diverse as the society becomes more complex, 31) it is advisable to believe in children's natural temperament and wait patiently for them to find their true identity despite how many trial and error. 32) One must intervene only when children can't figure out by themselves.…”
Section: How Can We Find Magic Sorting Hat Identity Identifier In Rementioning
confidence: 99%
“…El fenómeno hikikomori, traducido comúnmente como aislamiento social, es mundialmente conocido por el término japonés, por tener su origen en el país nipón y por ser este el que mayor número de casos reporta a día de hoy, a pesar de haberse extendido por otras partes del mundo desarrollado (Kato et al, 2012;Teo et al, 2015). Este fenómeno puede ser definido como "estado [...] que conlleva el encierro de uno mismo en su propio hogar, sin participar en sociedad durante seis meses o más, y que no parece tener otro problema psicológico asociado como su fuente principal" 2 (Saito, 2013).…”
Section: El Fenómeno Hikikomori: Definición Y Conceptounclassified